☆Who has the advantage? Race and sex differences in returns to social capital at home and at school. (September 2016) - Dufur, Mikaela J.; Parcel, Toby L.; Hoffmann, John P.; Braudt, David B.
Highlights: We examine the effects of family and school social capital on academic achievement. We study test scores for children who vary by race and sex. Girls obtain greater returns to family social capital than do boys. School social capital exerts no significant return on test scores to any group net of controls. Racial gaps in test scores are notable and deserve additional research. Abstract: A growing body of literature suggests that social capital is a valuable resource for children and youth, and that returns to that capital can increase academic success. However, relatively little is known about whether youth from different backgrounds build social capital in the same way and whether they receive the same returns to that capital. We examine the creation of and returns to social capital in family and school settings on academic achievement, measured as standardized test scores, for white boys, black boys, white girls, and black girls who were seniors in high school in the United States. Our findings suggest that while youth in different groups build social capital in largely the same way, differences exist by race and sex as to how family social capital affects academic achievement. Girls obtain greater returns to family social capital than do boys, but no group receives significant returns to school social capital after controlling for individual- and school-level characteristics.